Shared decision-making and patient decision aids in dermatology - Tan, Jerry; Linos, Eleni; Sendelweck, Myra A.; van Zuuren, Esther J.; Ersser, Steven; Dellavalle, Robert P.; Williams, Hywel C. (Wiley, 2016)
Shared decision making combines individual patient interests and values with clinical best evidence under the guiding principle of patient autonomy. Patient decision aids can support shared decision making and facilitate decisions that have multiple options with varying outcomes for which patients may attribute different values. Given the variable psychosocial impact of skin disease on individuals and relative uncertainty regarding best treatments and their adherence in many dermatological conditions, informed shared decision making, supported by patient decision aids, should constitute a central component of dermatological care.